Regional income convergence in Portugal (1991-2012) - Guerreiro, Gertrudes (2013)
Our research aims to address the problem of inequality in income distribution from a different perspective than the usual. We intend to verify if geography influences the pattern of inequality, that is, if the standard of living varies from region to region and if, in the process of growth, spatial units in Portugal have been converging in terms of most relevant variables, such as income. We search the answers to these questions by introducing the treatment of convergence between smaller territorial units, the municipalities as individuals. We intend to evaluate convergence or divergence in income growth and test empirically the theoretical hypothesis that β-convergence, although necessary, is not a sufficient condition for σ-convergence. To study convergence, we use information about GDP and wages for NUTS III regions, and wages for municipalities. We observe spatial dependence between municipalities, so we estimate spatial econometric models to test convergence. With regard to conditional convergence between municipalities, the model most appropriate is the one which includes in the explanatory variables the weight of primary sector employment, leading us to conclude that this variable distinguishes the "steady state" of the small economies. Variables like the activity rate and percentage of active population with higher education also reveal highly significant on the growth of wages, reflecting the different contexts of the labor market at regional level.